Clinical, Obstetrical, and Neonatal Outcomes after Single Euploid Frozen-Thawed Blastocyst Transfer with Subcutaneous Versus Intramuscular Progesterone Administration - Yarkiner, Zalihe; Boynukalin, Fazilet Kubra; Gultomruk, Meral; Coban, Onder; Bahceci, Mustafa (Gynecology Obstetrics & Reproductive Medicine, 2025)
Objective: To assess whether subcutaneous progesterone (SC-P) is non-inferior to intramuscular progesterone (IM-P) in terms of live birth rates and perinatal and obstetrical outcomes following single euploid embryo transfer. Study Design: This retrospective cohort study involved 350 participants who underwent single euploid blastocyst frozen embryo transfer (FET), comprising 219 recipients of intramuscular progesterone (IM-P) and 131 recipients of subcutaneous progesterone (SC-P). All embryo transfers were conducted within a hormone replacement therapy (HRT) protocol utilizing incremental oral estradiol valerate. Upon reaching an endometrial thickness exceeding 7mm, patients received either intramuscular progesterone (50 mg) or subcutaneous progesterone (50 mg) ten to thirteen days after priming. The primary outcome measures included live birth rates, as well as obstetrical and perinatal outcomes. Results: The clinical pregnancy rates were comparable between the intramuscular progesterone (IM-P) group (61.6%; 135/219) and the subcutaneous progesterone (SC-P) group (69.5%; 91/131, p=0.139). The live birth rates exhibited no significant difference between the IM-P group (49.8%; 109/219) and the SC-P group (58%; 76/131, p=,135). Miscarriage rates were also comparable, with 6.3% (22/135) in the IM-P group and 15.4% (14/91) in the SC-P group (p=0.854). Furthermore, there were no statistically significant variances observed between the IM-P and SC-P groups regarding the median gestational age of all live-born neonates (38 weeks in both groups; p=0.183), birth weights (median of 3205g in the IM-P group versus 3335g in the SC-P group; p=0.073), and the incidence of pregnancy-induced hypertension (4.6% in the IM-P group versus 5.3% in the SC-P group; p=0.833). Conclusion: The study results offer clinical evidence indicating that subcutaneous progesterone (SC-P) demonstrates comparable efficacy in achieving live birth rates when compared to intramuscular progesterone (IM-P). Moreover, the findings suggest that SC-P does not pose an elevated risk for adverse obstetrical and perinatal outcomes.